FORMULATION AND IN VITRO EVALUATION OF ALGINATE BASED METRONIDAZOLE PERIODONTAL GEL - Ariyana; Sinurat, David; Ervina, Irma; HAKIM BANGUN, DAN (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objectives: The objectives of this study were to develop alginate based metronidazole periodontal gel for local microbes eradication in periodontal pocket, to study the effect of 0.5 and 1% Carbopol addition to alginate base on drug release and antibacterial activity of the gel, and to identify the effect of storage at room temperature for 3 months on chemical and physical stability of the gel. Methods: The 25% metronidazole periodontal gel was prepared using alginate gel alone and in combination with 0.5 and 1% Carbopol. All of prepared formulations were evaluated for the pH, drug release, and antibacterial susceptibility. Stability of formulations were studied for 3 months including drug content, color and viscosity. Results: The release of metronidazole from alginate gel showed sustained release properties. Within 300 minutes study, metronidazole released from formulations without Carbopol, with 0.5%, and 1% Carbopol were 40.17%, 47.67%, and 51.48%, respectively. Addition of 0.5 and 1% Carbopol did not significantly affect the drug release. All formulations showed excellent inhibition to Staphylococcus aureus. The largest zone of inhibition was found on formula without Carbopol, then followed by formula with 1% and 0.5% Carbopol. Storage at room temperature for 3 months caused slight degradation of metronidazole content and viscosity of all formulations. However, the color was not affected. Conclusions: It is concluded that metronidazole periodontal gel can be formulated using alginate base. The alginate based metronidazole periodontal gel has sustained release properties. All formulations have excellent antibacterial activity, and stable on storage at room temperature for 3 months.